Progress on the mechanism of Polycystin-1 in bone remodeling - Guo, JinShi; Hu, GuangXuan; Li, XiaoYing; Yi, XueJie; Chang, Bo; Li, Tao (Frontiers in Cell and Developmental Biology, 2026)
Polycystin-1 (PC-1), a transmembrane protein expressed on cell membranes, plays a vital role in cell signaling and intercellular adhesion. Existing studies have shown that PC-1 plays a pivotal role in bone remodeling and that PC-1 deficiency results in disrupted bone remodeling, which markedly affects bone mass and skeletal development. This review describes the molecular structure and biological function of PC-1 and analyzes the mechanism by which it maintains bone homeostasis and regulates osteoblast and osteoclast activity. Particular emphasis is placed on the role of PC-1 in mechanical force-triggered bone remodeling and its interaction with the transcriptional co-activator tafazzin. Moreover, this review outlines the potential applications of PC-1 in treating skeletal diseases, such as osteoporosis, fractures, and premature closure of cranial sutures, thereby providing a theoretical basis for future research.